2021
DOI: 10.3390/antibiotics10060743
|View full text |Cite
|
Sign up to set email alerts
|

Suppressive Antibiotic Treatment in Prosthetic Joint Infections: A Perspective

Abstract: The treatment of prosthetic joint infections (PJIs) is a complex matter in which surgical, microbiological and pharmacological aspects must be integrated and, above all, placed in the context of each patient to make the best decision. Sometimes it is not possible to offer curative treatment of the infection, and in other cases, the probability that the surgery performed will be successful is considered very low. Therefore, indefinite administration of antibiotics with the intention of “suppressing” the course … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…More importantly, Beldman et al defined receipt of chronic antibiotic suppression (CAS) as a treatment failure. CAS is a noncurative strategy to prevent PJI recurrence [ 17 , 18 ]. It is reported that more than one-third of patients aged >80 years with PJI were treated with CAS, and 60% of them were event-free at 24 months [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, Beldman et al defined receipt of chronic antibiotic suppression (CAS) as a treatment failure. CAS is a noncurative strategy to prevent PJI recurrence [ 17 , 18 ]. It is reported that more than one-third of patients aged >80 years with PJI were treated with CAS, and 60% of them were event-free at 24 months [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fever and signs of sepsis were considered indicators of possible systemic spread through bacteremia. Additionally, a new positive result of the LS was considered Definitions: COAS was defined as a strategy based on a "suppressive antibiotic treatment" in which the administration of antibiotics occurs in the long term or indefinitely over time with the aim of reducing symptoms and delaying or preventing the progression of PJI in cases not eligible for standard surgical treatment [14]. Limited to COAS monitoring, a positive objectivity for one or more of these signs was considered indicative of new exacerbation and failure of COAS: severe joint pain, warmth, redness, tenderness, effusion, restricted active and passive motion, and presence of new fistula or local dehiscence or decubitus.…”
Section: Methodsmentioning
confidence: 99%
“…54 Understanding the imprecision of flexible treatment durations adopted in the best interests of patients with recurrent or resistant infections (e.g., suppressive, prophylactic, or 'pill-in-pocket' antimicrobial plans) is difficult due to their relative rarity. [55][56][57][58]…”
Section: Decision Node 3: Stopping Antimicrobial Treatmentmentioning
confidence: 99%